Windows Vista annoyances - Karp, David A. (O'Reilly, 2007)
"Windows Vista contains enough quirks, unaccountable behavior, and bad design to vex anyone. Why suffer when you can take matters into your own hands? Windows Vista Annoyances offers a wide-ranging collection of solutions, hacks, and time-saving tips for working around the most irritating features and getting Vista to do much more than Microsoft intended."--Jacket